The big cheese ebook - John, Jory (The Food Group, 2023)
An Instant #1 New York Times Bestseller! Don't miss the seventh picture book in the #1 New York Times bestselling Food Group series from Jory John and Pete Oswald! The Big Cheese is the best at everything, and brags about it, too. When the annual Cheese-cathlon comes around, the Big Cheese is prepared to win, as always. But what happens when the quiet new kid, Wedge Wedgeman, comes out on top? Is a slice of humility all the Big Cheese needs to discover that some things are better than being the best? Jory John and Pete Oswald serve up another heaping plate of laughs and lessons with this empowering, witty, and charming addition to their #1 New York Times bestselling series! Check Out Jory John and Pete Oswald's other funny bestselling books for kids ages four to eight and anyone who wants a laugh: The Bad Seed The Good Egg The Cool Bean The Couch Potato The Smart Cookie The Sour Grape The Good Egg Presents: The Great Eggscape! The Bad Seed Presents: The Good, the Bad, and the Spooky! The Cool Bean Presents: As Cool as It Gets! The Bad Seed Goes to the Library The Good Egg and the Talent Show That's What Dinosaurs Do